Theoretical Study on S-Methyl-thiabenzene and Their Analogous via DFT Method - Kassaee, M.Z.; Vessally, E.; Arshadi, S.; Bekhradnia, A.K.; Esfandiari, M. (Asian Journal of Chemistry, 2010)
Molecular structures of S-methyl-thiabenzene and their analogue, 1Me(H)-3Me(H) are studied using ab initio calculations with DFT method and 6-311++G** basis set. These compounds have 6π-electrons with homoaromatic and ylide character. In contrast to planar conformer, the pyramidal conformer of 1Me(H)-4Me(H) is stable. The nature of structural bonds is investigated.